2021
DOI: 10.1172/jci.insight.130510
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cell division promotes therapeutic resistance in glioblastoma stem cells

Abstract: Asymmetric cell division (ACD) enables the maintenance of a stem cell population while simultaneously generating differentiated progeny. Cancer stem cells (CSCs) undergo multiple modes of cell division during tumor expansion and in response to therapy, yet the functional consequences of these division modes remain to be determined. Using a fluorescent reporter for cell surface receptor distribution during mitosis, we found that ACD generated a daughter cell with enhanced therapeutic resistance and increased co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…More “stem-like” GBM cells are known to have greater resistance to therapy [ 2 , 9 , 15 , 21 , 47 ]. To see whether the apoptotic cells were enriched or depleted for CSCs, we treated pGBM001 organoids with the above drugs for 6 days and double immunostained for SOX2 and CC-3.…”
Section: Resultsmentioning
confidence: 99%
“…More “stem-like” GBM cells are known to have greater resistance to therapy [ 2 , 9 , 15 , 21 , 47 ]. To see whether the apoptotic cells were enriched or depleted for CSCs, we treated pGBM001 organoids with the above drugs for 6 days and double immunostained for SOX2 and CC-3.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from this study advance our understanding of these critical aspects of GBMs in several ways. First, recent work has identified numerous epigenetic and metabolic factors as essential for promoting GBM stemness and consequently as worthwhile therapeutic targets [8][9][10][11][21][22][23]. In particular, it has been shown that the guanine synthesis arm of purine metabolism can be targeted for overcoming GBM stemness [24].…”
Section: Resultsmentioning
confidence: 99%
“…However, a newer model suggests that CSCs are not necessarily rare or quiescent and that they can also arise by dedifferentiation and reprogramming of non-CSCs [206]. Similar to normal stem cells, CSCs may undergo symmetric-cell division to self-propagate; asymmetric-cell division to produce more differentiated progeny and self-renew; or they may become quiescent, depending on the stimuli the cell receive [208][209][210][211]. However, within the context of dysregulated signalling and genetic/epigenetic aberrations, the same processes that tightly control embryonic development, tissue regeneration, or wound healing are derailed in cancer.…”
Section: Tme Induces a Cancer Stem Cell (Csc) Phenotypementioning
confidence: 99%